When 'political demand' meets 'video-politics'. (2nd July 2016) - Tie, W
ABSTRACT: The emergence of a 'macro-personification of politics' within the political field of Aotearoa New Zealand alters the manner by which political demand needs to now operate if it is to succeed as a form of tactical strategy in political activism. A particular analytical initiative is identified as being central to success under these conditions, whereby given political demands enlarge from a 'state of singularity' to become 'complex discursive demands'. Key to that initiative is the 'dialectic of appearances' and the 'labour of the negative' associated with the ideas-work of Hegel. This article identifies how this dynamic was playing out within a key event in the anti-surveillance movement of 2013, the August public rally in the Auckland Town Hall.